Money and inflation in a nonlinear model - George, D.; Oxley, Leslie (Elsevier Science, 2008)
A nonlinear model of inflation and growth, with a fixed rate of money growth, is developed and its global dynamics analysed. These are compared with the local, linearised dynamics of the model. It is shown that the global dynamics of the model plausibly predict hyperinflationary bubbles, which are not present in the linearised version. Numerical simulations of the model are presented. © 2008 IMACS.